2014
DOI: 10.1111/eje.12111
|View full text |Cite
|
Sign up to set email alerts
|

Dental students' reflective habits: is there a relation with their academic achievements?

Abstract: To foster reflective thinking, tutoring should primarily be focused on younger students (≤23 years old) and those without a previous university degree. Further, a wide variety of assessment methods is suggested to stimulate different reflective constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 61 publications
8
23
1
2
Order By: Relevance
“…This could be due to the fact that females tend to have a positive attitude toward their profession, do not avoid taking responsibility, and act sincerely. [20] This finding disagreed with our results along with the other similar studies by Lew and Schmidt[5] and Tricio et al [2] in which no significant gender differences were observed.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This could be due to the fact that females tend to have a positive attitude toward their profession, do not avoid taking responsibility, and act sincerely. [20] This finding disagreed with our results along with the other similar studies by Lew and Schmidt[5] and Tricio et al [2] in which no significant gender differences were observed.…”
Section: Discussioncontrasting
confidence: 99%
“…[1] Self-directed learning is a vital principle promoted in health profession's education, particularly with the increasing use of online learning methods. Self-directed learning as defined by Knowles is “a process in which individuals take the initiative, with or without the help of others, in diagnosing their needs, formulating learning goals, identifying human and material resources for learning, choosing and implementing appropriate learning strategies, and evaluating learning outcomes.”[2]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile of competences is organised into 5 domains, highlighting the concepts of professionalism, safe and effective clinical practice, a patient‐centred approach and the place of dentistry in society . Similarly, many measures are intended to even out the historical gap between the pre‐clinical and clinical stages, to promote early clinical experience, vertically integrated curricula, and to develop self‐reflection and reflective practices …”
Section: The Current Situation Of Dental Educationmentioning
confidence: 99%
“…10 Similarly, many measures are intended to even out the historical gap between the pre-clinical and clinical stages, to promote early clinical experience, vertically integrated curricula, and to develop selfreflection and reflective practices. [11][12][13]…”
Section: Dental Education Is Evolvingmentioning
confidence: 99%